Dynamics Response of the Proton Exchange Membrane Fuel Cell Coupled with Electrolysis - Made Sucipta; I Gede Febri Bala Antara; Richard Butarbutar; Made Suarda; I Nyoman Budiastra; I Gusti Ngurah Janardana (Journal of Renewable Energy and Environment)
Fuel cells convert the chemical energy of reactants into electrical energy, with the Proton Exchange Membrane Fuel Cell (PEMFC) being a prominent example due to its simple structure, durability, and ease of operation. The power output of a PEMFC is influenced by the number of cells in the stack, provided there is an adequate supply of hydrogen. This experiment investigated how varying the number of cells affects the dynamic response of PEMFC output power, while maintaining a constant hydrogen flow rate produced by a 4-Volt DC electrolyzer. Stacks with 4, 7, and 10 cells were tested, each with resistance variations of 100, 150, 200, and 300 Ohms. Under Open Circuit Voltage conditions, the stack with 10 cells exhibited the highest maximum voltage. Conversely, the lowest power output was observed for the 4-cell stack. When loaded, the 7-cell stack generated higher output power as hydrogen was effectively utilized by all cells. However, the 10-cell stack produced lower power output than the 7-cell stack due to insufficient hydrogen supply. Thus, increasing the number of cells requires a corresponding increase in hydrogen supply. The findings of this experiment provide insights for future design considerations in fuel cell power systems.